School activities and tasks in initial teaching education: an analysis of written statements - Sousa, Adna; Rodrigues de Souza, Clara Regina (DISCURSIVITIES, 2022)
The present article contemplates a study about the elaboration of writing activities, in the context of initial teacher education. We know that developing school activities and tasks is a practice inherent to teaching, since the teacher constantly produces activities applied in the classroom, to mobilize students' knowledge in the learning process. However, sometimes this practice needs to be systematized in undergraduate courses. From this perspective, we developed methodology in which we investigate the production of wordings of writing activities elaborated by pre-graduating students of the Portuguese Language Arts Course. To this, we are based on Araújo (2014), which deals with wordings of activities; Antunes (2003; 2009), which discusses writing activity. The results of the analysis point to the fact that teachers in initial education, despite having no experience with the practice of elaborating wordings, demonstrate a satisfactory development in the writing activities elaborated.